Dynamics of cytokine induced E-selectin expression in endothelial cells - Ogrodzinski, Lydia (2023)
E-selectin is a cell adhesion molecule, expressed on the cell surface of endothelial cells in response to inflammatory cytokines. Once expressed, E-selectin mediates tethering and rolling of circulating leukocytes so that they can be extravasated to inflamed tissue. Excessive recruitment of leukocytes is often a symptom of inflammatory disease, therefore the study of cytokine regulation of expression would aid understanding of how to combat this process in cases where there is over stimulation. In addition, targeting and inhibiting E-selectin expression has been a popular route to repress inflammatory progression in many diseases. Unfortunately, E-selectin - targeting therapeutics that have reached clinical trials have not been efficacious in ameliorating inflammatory symptoms or targeting E-selectin specifically. This thesis explored E-selectin regulation by key inflammatory cytokines, considered membrane organisation of expressed E-selectins and created multiple in vitro models to measure expression, aid detection of specific E-selectin drug binding and quantify E-selectin internalisation. To begin, E-selectin expression was studied in human umbilical vein endothelial cells (HUVECs), using an anti-E-selectin monoclonal antibody. Binding of fluorescent secondary antibody enabled detection of expression over time using confocal microscopy, and alkaline phosphatase secondary antibody binding enabled quantification of E-selectin using principles of enzyme-linked immunosorbent assay (ELISA) in fixed cells. Here, TNF alpha time course and concentration responses were quantified, and it was discovered that VEGF165a and histamine enhanced the TNF alpha response as well as induced E-selectin expression alone at lower levels. An improved model was then created with increased sensitivity and the ability to measure E- selectin expression in real time in live cells using a split NanoLuciferase binary technology (NanoBiT). A multitude of inflammatory cytokines could then be ranked in order of potency for inducing E-selectin expression and kinetics assays over 15 hr were performed to detect expression dynamics. Here it was found that TNF alpha was the most potent cytokine which exhibited maximal expression over 15 hr, contrary to other cytokines where expression decreased by 50% after 8 hr stimulation. The E-selectin membrane organisation was then defined using principles of bioluminescence resonance energy transfer (BRET) between NanoLuc tagged E-selectin and fluorescent tagged selectin family. Here, E-selectin homodimers were identified and heterodimers between E- and L-selectin was discovered, whereas no interactions were quantified between E-selectin and P- selectin. Finally, BRET interactions between a fluorescently conjugated E-selectin binding peptide (Esbp) were quantified for two fluorescent conjugations; Alexa Fluor (AF) 633 and AF488, however, no interactions were observed most likely due to steric hindrance of fluorophores. However, unlabelled Esbp induced E-selectin internalisation in models using fluorescently labelled SNAP-tag E-selectin in human embryonic kidney (HEK)293T cells and HiBiT tagged E-selectin in HUVECs. The findings demonstrated the graded stimulation of E-selectin expression by inflammatory cytokines, and further observed interactions of E-selectin with selectin family members on the membrane. In addition, peptide induced internalisation of E-selectin was observed, and the potential for all in vitro systems created to determine specific drug binding is discussed in detail.